Avaliação de frações antigênicas de Taenia crassiceps obtidas por hidrofobicidade, no imunodiagnóstico das formas ativa e inativa da neurocisticercose humana em amostras de líquido cefalorraquidiano - Silva, Gabriela Borges da (2016)
The neurocysticercosis (NCC) is parasitic disease that affects the human central nervous system (CNS) and is caused by metacestodes of Taenia solium. NCC is a pleomorphic disease due to differences in the number and location of the lesions and the severity of the immune reaction of the host against the parasite. Despite advances in neuroimaging and immunological tests, NCC diagnosis still is a challenge due to the nonspecific clinical manifestations. The difficulty of obtaining metacestodes of naturally infected pigs has stimulated the search for heterologous antigens, such as Taenia crassiceps, kept in experimental model. The study aimed to evaluate the total extract of metacestodes of Taenia crassiceps (SE) and its antigenic fractions (detergent - DF and aqueous - AF) obtained by hydrophobicity through the use of Triton X-114, applied in na alternative method for the immunological diagnosis of active and inactive human NCC in cerebrospinal fluid (CSF), a low cost and rapid technique. The total saline extract of metacestodes of T. crassiceps and their antigenic fractions were tested by ELISA (enzyme-linked immunosorbent assay) for detection of immunoglobulin G (IgG). DF and AF showed high sensitivity (Se) and specificity (Sp) indexes in immunodiagnosis of active or inactive NCC (100% ) when compared with saline total extract (Se = 100% and Sp = 93%, active; Se = 95% and Sp = 93%, inactive). The results demonstrated that both fractions, DF and AF are important, efficient and potentially applicable in the diagnosis of active and inactive NCC